(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Compared to other businesses, tourism is one of the fastest expanding sectors due to low capital expenditure. Since ancient times, religious tourism has been one of the more significant forms of travel. Due to its geographical features, including its position, lovely terrain, enjoyable waterbodies and waterfalls, and historic religious sites, the Haveli tehsil of the Pune district has a great deal of potential to expand the tourism business. For the development of a pilgrim tourist destination, pilgrims’ satisfaction with the services already offered in the tourist centre is crucial. The current study’s objective is to gauge pilgrim happiness at Dehu, known for Vari, Varkari and „Paalkhi‟ from Dehu to Pandharpur in month of Ashad. .The goal of the current study is to comprehend satisfaction